2008
DOI: 10.1245/s10434-008-0030-z
|View full text |Cite
|
Sign up to set email alerts
|

Combined Axillary Reverse Mapping (ARM) Technique for Breast Cancer Patients Requiring Axillary Dissection

Abstract: This technique of combined isotopic and blue dye ARM and findings must now be validated. A multicentric study is planned to confirm this data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
91
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 18 publications
9
91
0
1
Order By: Relevance
“…The positive RAM node was identified in pN3 axilla(high stage axillary disease). The same pattern had been described in various studies in literature, which have shown a positive relation between high nodal positivity and chance of arm lymphatics also being involved by the disease [9,10,17,19,20] Schunemann Jr et al, found a statistically significant association between occurrence of metastasis in RAM nodes and high nodal disease(P<.0.001) [19]. Most studies thus suggest that performing RAM in patients with high nodal disease, is not oncologically sound [10,11,17,19] .…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The positive RAM node was identified in pN3 axilla(high stage axillary disease). The same pattern had been described in various studies in literature, which have shown a positive relation between high nodal positivity and chance of arm lymphatics also being involved by the disease [9,10,17,19,20] Schunemann Jr et al, found a statistically significant association between occurrence of metastasis in RAM nodes and high nodal disease(P<.0.001) [19]. Most studies thus suggest that performing RAM in patients with high nodal disease, is not oncologically sound [10,11,17,19] .…”
Section: Discussionsupporting
confidence: 83%
“…Rate of Identification of arm lymphatics varies from 33.3% in initial studies to as high as 91% with use of radio isotopes, [8,9]. In our study, using methylene blue dye injection, at the start of surgery, blue lymphatics were identified in72.2 % while blue lymph nodes could be identified in 61.1%.The pattern of distribution of arm lymphatics in axilla varies with respect to axillary vein .…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations